First time identification of Pandoraea sputorum from a patient with cystic fibrosis in Argentina : a case report - Martina, Pablo Francisco (2017)
Fil: Martina, Pablo Francisco. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico (Nordeste). Instituto de Biología Subtropical. Instituto de Biología Subtropical. Nodo Posadas; Argentina.